1996
DOI: 10.1074/jbc.271.51.32714
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyanthranilic Acid Is an Efficient, Cell-derived Co-antioxidant for α-Tocopherol, Inhibiting Human Low Density Lipoprotein and Plasma Lipid Peroxidation

Abstract: ␣-Tocopherol (␣-TOH) can promote lipid peroxidation in human low density lipoprotein (LDL) unless co-antioxidants are present that eliminate the chain-carrying ␣-tocopheroxyl radical (␣-TO ⅐ ) (Bowry, V. W., Mohr, D., Cleary, J., and Stocker, R. (1995) J. Biol. Chem. 270, 5756 -5763). Interferon-␥ inhibits human monocyte/ macrophage-facilitated LDL lipid peroxidation via induction of cellular tryptophan degradation and production and release of 3-hydroxyanthranilic acid (3HAA) (Christen, S., Thomas, S. R., Gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 55 publications
2
56
0
Order By: Relevance
“…Our subsequent studies reported that 3-HAA is an efficient antioxidant capable of inhibiting LDL oxidation induced by a variety of oxidants, involving the ability of 3-HAA to scavenge oxidants (e.g. peroxynitrite) or act as a co-antioxidant, referring to its ability to efficiently reduce the vitamin E radical, ensuring the reduced and antioxidant form of vitamin E is maintained within LDL [345,346].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 98%
“…Our subsequent studies reported that 3-HAA is an efficient antioxidant capable of inhibiting LDL oxidation induced by a variety of oxidants, involving the ability of 3-HAA to scavenge oxidants (e.g. peroxynitrite) or act as a co-antioxidant, referring to its ability to efficiently reduce the vitamin E radical, ensuring the reduced and antioxidant form of vitamin E is maintained within LDL [345,346].…”
Section: Transplantation the Ultimate Goal In Organ Transplantationmentioning
confidence: 98%
“…Most studies of LDL lipid peroxidation in vitro utilize lipoproteins removed from native environments, although it is now recognized that such environs play an important role in the antioxidant function of vitamin E. For example, a number of endogenous reducing agents, termed "coantioxidants," can impede the pro-oxidant activity of ␣-TOH (79,666,949,1059). As depicted in Figure 9, coantioxidants (denoted as XH) reduce the ␣-TO⅐ and eliminate the radical character from the LDL particle, thereby inhibiting tocopherol-mediated peroxidation.…”
Section: E Inhibition Of Ldl Oxidationmentioning
confidence: 99%
“…3-Hydroxyanthranilic acid (3-HAA) is a further KP product that is a potent free radical scavenger [103] , which may have some neuroprotective effects. In IFN-␥ -stimulated macrophages, 3-HAA inhibits peroxidation of LDL by acting in synergy with ␣ -tocopherol [104] . It remains to be seen whether enough 3-HAA is produced in vivo to have these benefi cial effects.…”
Section: Direct Evidencementioning
confidence: 99%